(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
This paper focuses on the review report on the Non-Conventional Energy Scenario in India. Fossil fuels are the main fuel for the energy generation for the worldwide, but it is limited in nature for the next few generations. Therefore, the generation has to change the source of energy from fossil fuels to the current trending energy resources such as non-conventional energy resources. Most of the India Energy Generation is based on conventional energy sources which focus on coal and oil energy and they are limited in nature. Conventional sources are non-bio-degradable and cause more pollution. Whereas non-conventional energy is pollution free source for energy.